Pre-slaughter stress mitigation in goats: prospects and challenges - Kumar, Pavan; Abubakar, Ahmed Abubakar; Ahmed, Muideen Adewale; Hayat, Muhammad Nizam; Kaka, Ubedullah; Pateiro, Mirian; Sazili, Awis Qurni; Hoffman, Louwrens C.; Lorenzo, Jose M. (Elsevier, 2023)
Over the years, the handling of goats (loading, transport, unloading, time spent in lairage) prior to slaughter as well as the slaughter process (stunning, and bleeding) has largely applied to other livestock which impairs the wellbeing of goats as well as their products due to the difference in behavior among species. Numerous factors (feeding management, production systems, environmental conditions, and physiological status of the animals) predispose goats to pre-slaughter stress, resulting in increased stress responses during the transport, lairage, and slaughter process that influence the meat quality attributes. Goats are more susceptible to pre-slaughter stress relative to other ruminants. In this review, stress factors relating to goats, indicators as well as management, were elucidated which will assist producers in making informed decisions on minimizing goat stress for the betterment of the meat quality and goat industry as a whole.